ANALISIS INDIKATOR DAN STANDAR PENETAPAN KELUARGA MISKIN PADA BADAN PUSAT STATISTIK KABUPATEN ACEH TENGGARA - Roezaini Sofie (Jurnal Mahkota Bisnis (Makbis), 2024)
This research is motivated by the fact that the concept of poverty in Indonesia has developed over time. Likewise, the existence of a distinction or difference in principle between the government and sharia regarding the nomenclature of the poor and needy requires all parties to reformulate the concept of poverty. The method used in this study is a descriptive qualitative method. While this type of research is a type of library research. This research was conducted by collecting library data without being followed by empirical testing. While the approach to this research uses a normative socio-economic approach, where this paper seeks the essence of each value of Islamic teachings to then be transformed into forms of socio-economic activities. The results of this study are that the clear distinction between the government and Islam can be mediated by the role of 'urf and 'adah to then find a clear synchronization point regarding poverty in Indonesia according to the Islamic perspective. The goal, first, is that these findings can be projected as a basis for formulating standardization of mustahiq zakat, especially the poor in Indonesia. Second, the terminology of the poor and needy who are included in the asnaf ats-tsamaniyah group of zakat recipients can be translated and interpreted contextually according to the economic situation and conditions in Indonesia based on real data on poverty conditions in Indonesia. Third, the large potential of zakat in Indonesia can be utilized by the government as an economic empowerment program based on zakat and based on the welfare of the community for the poor and needy in Indonesia.